Development and validation of a French Canadian version of the falls Behavioral (FaB) Scale. (October 2014) - Filiatrault, Johanne; Demers, Louise; Parisien, Manon; Lorthios-Guilledroit, Agathe; Kaegi, Christine; Ménard, Isabelle; Paniconi, Mary-Grace; St-Laurent, Caroline
Abstract Purpose: To develop a French Canadian version of the Falls Behavioral (FaB) Scale and examine its psychometric properties. Methods: The FaB was adapted in French Canadian (FaB-FC) and validated according to standard guidelines for cross-cultural adaptation of questionnaires. The internal consistency and construct validity of the FaB-FC were studied among 64 community-dwelling adults aged 60 and over. The concurrent validity and test–retest reliability of the FaB-FC were respectively examined among subsamples including 31 bilingual and 33 unilingual participants. Results: The FaB-FC showed good concurrent validity with the original FaB (ICC2 = 0.94; 0.87–0.97), as well as good test–retest reliability (ICC2 = 0.94; 0.88–0.97). The FaB-FC also demonstrated high internal consistency (α = 0.91). Moreover, analyses showed significant associations of the FaB-FC scores with fear of falling and balance confidence scores, attesting to its construct validity. Conclusion: This study provides evidence that the FaB-FC has sound psychometric properties. Since falls are associated with multiple risk factors, including behavioral factors, the FaB-FC is undoubtedly a relevant assessment tool for clinicians and researchers working toward fall prevention among French-speaking community-dwelling seniors. Implications for Rehabilitation Fall-related behaviors should be addressed in the assessment of community-dwelling seniors' fall risks. Like the original FaB, the French Canadian version of the tool (FaB-FC) is valid and reliable for assessing fall-related behaviors. The FaB-FC is a relevant complementary assessment tool for identifying seniors at risk for falls. The FaB-FC could also be useful in guiding fall prevention interventions and measuring the impact of these interventions on seniors' behaviors.